Hikmah dalam al-Qurâ€™Än dan Implementasinya dalam Membangun Pemikiran Islam yang Inklusif - Zamzami, Mukhammad (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2016)
This article attempts to trace and describe the correlation of ?ikmah (wisdom) and inclusivity in the Qur??n along with their connection to the dynamics of development of contemporary Islamic thought. ?ikmah in its implied meaning as wisdom of thinking?which puts emphasis on reason, acquirement, and ability?has been compatible with the inclusivity of Islamic thought in several aspects. Such inclusivity can be observed, among others, within the following aspects, are: firstly, inclusive refers to tolerance and it implies acceptance toward plurality, heterogeneity, and self-willingness to actively participate in it. Inclusive thought brings about tolerance. Tolerance explicitly comprises conformity with wisdom in which each entity highly emphasizes public benefit. Secondly, inclusive means freedom. Freedom requires one?s discretion to use reason as a means of truth search. This meaning is closely related to wisdom, which perceives thinking and reasoning as a way to reach the truth. Thirdly, inclusive also means freedom. Freedom necessitates a universal and non-coercive Islamic thought. Terminologically, it has similar meaning to wisdom where each side lays emphasis on the implementation of a universal Islamic thought. Islam provides its adherents wide space to freely choose their way of life, including right to embrace certain religious ideology.